Chronic Non-Productive Cough in Patients With Primary Sjögren’s Syndrome - Gonca DOĞRU; Ayşe BALKARLI; Atalay DOGRU (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate the frequency of chronic cough due to dryness in the trachea and the relationship between depression and chronic cough in patients with primary Sjögren’s syndrome (pSS). Patients and methods: Eighty non-smoking patients (7 males, 73 females; mean age 47.6±9.2 years; range 18 to 70 years) with newly diagnosed pSS were included. All patients were evaluated clinically, radiologically, and physiologically. Patients with cough were assessed using the Leicester Cough Questionnaire and visual analog scale. Beck Depression Inventory was used to determine the risk of depression in patients with cough. Patients with asthma, rhinosinusitis, gastrooesophageal reflux, and drug use which cause cough and pulmonary involvement in pSS were excluded. Results: Non-productive cough was detected in 30 patients (37.5%). Fourteen patients (17.5%) were admitted to the hospital with cough at least once before the diagnosis of pSS. The median time between onset of symptoms and firm diagnosis was 24 months (25-75 interquartile ranges: 3-60 months). A significant difference was observed in the Beck Depression Inventory scores between patients with and without cough. There was a significant negative relationship between Leicester Cough Questionnaire and Beck Depression Inventory scores. Conclusion: Patients with pSS often have symptoms for a long duration that mimic those of more commonly encountered non-specific pulmonary conditions. Xerotrachea should be considered in the differential diagnosis of chronic cough, especially in patients with normal pulmonary function tests and pulmonary imaging.